Understanding COVID-19 vaccine hesitancy in health care professionals in Central and West Asia: lessons for future emergency mass vaccination campaigns - Adambekov, Shalkar; Bongers, Alexander; Hare, Jonathan; Popovic, Dragoslav; Rajashekharaiah, Harsha; Lawson, Stefan M.; Riggall, Giovanna; Kokareva, Larissa; Chin, Brian (Frontiers in Public Health, 2023)
A Quick Assessment of Vaccine Hesitancy approach was developed to collect population insights on vaccination hesitancy for low resource environments. Insights into COVID-19 vaccine hesitancy were collected through online webinars with heads of healthcare departments and anonymized online surveys of healthcare managers (HCM) and primary healthcare workers (HCW) in four countries in Central and West Asia (Armenia, Georgia, Tajikistan, and Kyrgyzstan) between 28 February 2022 and 29 March 2022. From the responses to the survey some key themes identified that underpinned in vaccine hesitancy across the region were perceived understanding of vaccine efficacy, conflict with individual religious beliefs, concerns for side effects, and the relatively rapid development of the vaccine and that improving communications strategies to address these concerns would be critical in combatting vaccine hesitancy through any future public health emergencies.